STUDENT SATISFACTION WITH FACILITY PROVISION AND QUALITY IN NUHU BAMALLI POLYTECHNIC ZARIA, KADUNA STATE, NIGERIA - Sadiya Danjuma; Maryam M. Salihu; Muhammad Hassan (Western European Studies, 2023)
Despite the fact that measures are being taken to improve the educational system in Nigeria attractive and functional, there is a growing concern over the alarming rate of students’ low satisfaction with facilities in school. Therefore, the study analyzed student satisfaction with facilities provision and quality in Nuhu Bamalli Polytechnic, Zaria with a view to enhance the quality of facilities management practice. The study adopted a quantitative approach, where data was collected using questionnaires from 341 students which were randomly selected from 4 schools in Nuhu Bamalli Polytechnic, Zaria: School of Environmental Studies, School of Engineering Technology, School of Applied Science and School of Liberal Studies. The data were analyzed using descriptive statistics. The study revealed that Students in Nuhu Bamalli Polytechnic, Zaria were averagely satisfied with ICT, sports, health, classroom, library, and laboratory facilities. While their satisfaction level with hostel, securities, workshop and studio facilities were low. It was recommended that The management of the Polytechnic should focus on policies that target adequate provision of facilities and services that the students were not satisfied with in the Polytechnic. The Polytechnic should be responsive to the expectations and needs of the students in order to improve their satisfaction
Keywords: Student; Satisfaction; Provision; Quality